(untitled) (Update Dental College Journal, 2014)
Extraction of premolar teeth to manage class I malocclusion is conventionally the management approach of choices. However class I malocclusion with tooth tissue discrepancy could be manage with the extraction of a lower incisor tooth with a more acceptable aesthetic outcome. This article describe a cases of class I malocclusion mange with extracting a mandibular lower incisor tooth. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17987 Update Dent. Coll. j: 2013; 3 (1): 54-57